O lugar do conhecimento especializado em audiodescrição na análise dos elementos narratológicos dos roteiros autoral e original traduzido de audiodescrição do filme 'Um lugar silencioso' - Mariana Musse Furtado (2024)
Audio description (AD) is a form of accessible audiovisual translation that involves translating from the visual mode into the verbal mode, with a view to providing visually impaired people with access to visual information such as those in movies, theatrical plays, museum exhibitions, and television shows. It enables visually impaired people to comprehend these works fully, ensuring their inclusion in society without the need for a sighted person’s assistance. Within Audiovisual Translation Studies, AD falls under the category of intersemiotic translation, as it involves translation across two different semiotic systems. This MA thesis aims to reflect on the role of specialized knowledge in the production of audio description, considering that AD is a specialized function that requires expertise. The study used a corpus consisting of two Portuguese AD scripts (one translated and one original) of the movie "A Quiet Place", with a focus on the object labels (AMB_OBJ) within their narratological elements. From a process perspective, the research analyzed the essential procedures to achieve well-executed AD, considering it as a specialized function. Building on Corpus Linguistics, it employs a descriptive and exploratory methodology. It uses film narratology as a tool to describe the structures of the AD scripts both qualitatively and quantitatively. It identifies the occurrences of narratological elements and discusses the quantitative findings. Software Subtitle Workshop was used to produce the original AD script and transcribe the original AD script. Software suite WordSmith Tools 8.0 was used to analyze the manually inserted corpus tags – more specifically, its Concord and Wordlist tools were used to search for character description tags and their occurrences in the ADs. The findings showed that specialized knowledge of AD can contribute to producing a more comprehensive AD script, one which facilitates the understanding of the movie by the visually impaired and the importance of objects to complement an audio description script.